Electromedical Biosensors for the Detection of Diseases - Yang Zeyu (MATEC Web of Conferences)
Infectious illnesses are harmful to all organisms, including animals and plants. The detection of the virus is limited by the level of virus number and the symptom of the patient. In order to observe the existence of a virus in time and get more time for the healthcare work for the patient, the development of an electromedical biosensor that can detect the existence of the pathogen is essential. This essay mainly discusses the structure and the principle of the new form of biosensor. During the process of researching, the author took a look at the related essays in this field to make a correct description of all the nouns mentioned in the article. The electromedical biosensor has three main components: the electrode, the biosensor elements, and immobilization and surface passivation. Every component has its own function, such as transportation and dating. The result shows that the electromedical biosensor has advantages such as higher sensitivity and wider detection limit.